Determinants and Effects of Countries' External Capital Structure : A Firm-Level Analysis - Herman, Uros (IMF Working Papers; Working Paper ;, 2022)
In this paper, we investigate whether a firm's composition of foreign liabilities matters for their resilience during economic turmoil and examine which characteristics determine a firm's foreign capital structure. Using firm-level data, we corroborate previous findings from the (international) macroeconomic literature that the composition of foreign liabilities matters for a country's susceptibility to external shocks. We find that firms with a positive equity share in their foreign liabilities were less affected by the global financial crisis and also less likely to default in the aftermath of the crisis. In addition, we show that larger, more open, and more productive firms tend to have a higher equity share in total foreign liabilities.